Profil Pengunaan Opioid untuk Mengelola Nyeri di Rumah Sakit Negeri di Bali - Ernawati, Desak Ketut; Widatama, Agata (Jurnal Ilmiah Medicamento, 2025)
Opioids are the mainstay of pain management, particularly in chronic pain-related and nonrelated cancer. Studies have shown that the number of opioids used globally varies. It was used excessively in some parts, while in others, it was underused. Little study is known on how opioids are used in Indonesia. This study aimed to identify indications of opioids prescribed and types of opioids used, as well as assess the nature of opioid therapy as pain management for chronic and non-related cancer. This retrospective study was conducted in a public hospital in Bali, Indonesia. Data was collected from all inpatients who received opioids in the hospital from 2018 to 2020. Patients’ age, gender, as well as opioid information such as types of opioids and used for treatment for cancer or non-cancer patients, were pooled and analyzed descriptively. This study found that fentanyl injection was the most opioid prescribed by anesthesiologists as preoperative medications. Opioids were prescribed mostly for non-cancer patients, and limited opioids were prescribed for cancer patients. Future research is required to evaluate factors that influence opioid prescriptions in hospitals.